2022
DOI: 10.48550/arxiv.2201.13078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lymphoma segmentation from 3D PET-CT images using a deep evidential network

Ling Huang,
Su Ruan,
Pierre Decazes
et al.

Abstract: An automatic evidential segmentation method based on Dempster-Shafer theory and deep learning is proposed to segment lymphomas from three-dimensional Positron Emission Tomography (PET) and Computed Tomography (CT) images. The architecture is composed of a deep feature-extraction module and an evidential layer. The feature extraction module uses an encoder-decoder framework to extract semantic feature vectors from 3D inputs. The evidential layer then uses prototypes in the feature space to compute a belief func… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…One evidence comes from a probabilistic model, and the other comes from an evidential model. Paper (Huang et al, 2021b) and (Huang et al, 2022) confirmed the similarity of ENN and RBF when acting as an evidential classifier and applied both the two models within a deep neural network for lymphoma segmentation. We think more achievements could be obtained by cooperating BFT and popular deep medical image segmentation model, such as UNet, VNet (Milletari et al, 2016) and nnUNet (Isensee et al, 2018), in the future.…”
Section: Future Workmentioning
confidence: 60%
See 4 more Smart Citations
“…One evidence comes from a probabilistic model, and the other comes from an evidential model. Paper (Huang et al, 2021b) and (Huang et al, 2022) confirmed the similarity of ENN and RBF when acting as an evidential classifier and applied both the two models within a deep neural network for lymphoma segmentation. We think more achievements could be obtained by cooperating BFT and popular deep medical image segmentation model, such as UNet, VNet (Milletari et al, 2016) and nnUNet (Isensee et al, 2018), in the future.…”
Section: Future Workmentioning
confidence: 60%
“…Radial basis function (RBF) network. As confirmed in (Huang et al, 2022) that RBF network can be an alternative approach of ENN that based on the aggregation of weights of evidence.…”
Section: The Likelihood-based Classifiermentioning
confidence: 80%
See 3 more Smart Citations